Sistem Informasi Manajemen Outbound Call (OBC) Subunit Payment Collection Pada Witel Lampung Berbasis Web - Wartariyus; Edo Laksana Widodo; Rendy Lutfi Prabowo; Muhammad Dzaki Arrahman (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
The regional division of PT. Telekomunikasi Indonesia (Telkom) in Lampung, known as Witel Lampung, is responsible for managing telecommunication services for customers in the area. However, the current manual process of recording outbound call data in Microsoft Excel spreadsheets poses challenges in terms of accuracy, reliability, and efficiency. This affects the decision-making process of finance officers who rely on this data to calculate various metrics and indicators. To address these challenges, Witel Lampung requires an information system that can automate the process of collecting, storing, and analyzing outbound call data. The main objective of this research is to design and develop a user-friendly front-end system for finance officers to automatically calculate outbound call data. The implementation of this system will improve data accuracy and reliability, reduce time and effort required for data management, and enhance the overall efficiency of Witel Lampung's operations, resulting in better customer service and satisfaction. Investing in this system will help Witel Lampung improve its data management capabilities, decision-making process, and overall competitiveness in the telecommunications industry.